Contribution of PPP with Ambiguity Resolution to the Maintenance of Terrestrial Reference Frame - Ruyuan Wang; Junping Chen; Yize Zhang; Weijie Tan; Xinhao Liao (Remote Sensing)
Precise Point Positioning (PPP) provides static positioning at the millimeter level and kinematic positioning ranging from millimeters to decimeters globally. Unlike the traditional network solution, PPP does not require data from other reference stations. This flexibility enhances the convenience of densifying the reference frame while maintaining the accuracy of solutions. In this study, Precise Point Positioning with Ambiguity Resolution (PPP-AR) was employed instead of a network solution, utilizing the combined orbit, clock, and bias products from IGS Repro3 to resolve the long-term station coordinates and derive their velocities, thereby contributing to the maintenance and densification of the terrestrial reference frame. We selected 46 globally distributed stations and performed PPP-AR over a 5-year period, from 2015.0 to 2020.0. The results show that differences in station coordinates between PPP-AR and IGS Repro3 are almost within 2 mm in the horizontal direction and within 5 mm in the vertical direction after Helmert transformation, which is roughly equivalent to the formal error of IGS solutions. The velocity uncertainty of PPP-AR solutions and the difference between PPP-AR and IGS Repro3 are nearly equal to the formal error of the ITRF horizontal velocity field and slightly exceed that of the IGS horizontal velocity field. The seasonal amplitudes of the remaining stations demonstrate strong consistency. Compared to PPP solutions, PPP-AR solutions provide improved coordinate and velocity precision, particularly in the east component. The consistency between the IGS Repro3 orbit/clock combination and IGS Repro3 position solutions is relatively high. These findings indicate that the PPP-AR technique can derive high-precision station coordinates with a similar level of accuracy to network solutions for supporting the maintenance and densification of the terrestrial reference frame.